CLIL-ПОДХОД В ОБУЧЕНИИ РУССКОМУ ЯЗЫКУ СТУДЕНТОВ ЖЕЛЕЗНОДОРОЖНЫХ СПЕЦИАЛЬНОСТЕЙ: ОПЫТ КОКАНДСКОГО ЖЕЛЕЗНОДОРОЖНОГО ТЕХНИКУМА (Лучшие интеллектуальные исследования, 2025)
Аннотация: Статья посвящена внедрению методики CLIL (Content and Language Integrated Learning — предметно-языковое интегрированное обучение) в преподавание русского языка студентам железнодорожных специальностей. Описывается опыт Кокандского железнодорожного техникума по интеграции профильных дисциплин (например, «Планирование работы дежурного по станции») с обучением русскому языку. В статье анализируются методические подходы, представлены результаты пилотного курса и обозначены перспективы дальнейшего развития.Abstract: The article focuses on the implementation of the CLIL (Content and Language Integrated Learning) methodology in teaching the Russian language to students of railway specialties. It describes the experience of Kokand Railway Technical School in integrating specialized disciplines (such as "Station Duty Planning") with Russian language instruction. The article analyzes methodological approaches, presents the results of a pilot course, and outlines prospects for further development.A small lyrical note: CLIL allows you to “kill two birds with one locomotive” — developing both language competence and professional knowledge simultaneously, which is especially relevant in the era of high-speed railway projects.